Image in communication: Polish high school students and teachers vis-à-vis the dynamic aspects of their image on the official internet website of their school - Bielak, Marlena Iwona (Scripta Neophilologica Posnaniensia, 2018)
Image in communication: Polish high school students and teachers vis-à-vis the dynamic aspects of their image on the official internet website of their school